Reconsidering Justice for Female Victims of Intimate Partner Violence: A Sociocultural and Legal Framework - Hakim, Fany Nur Rahmadiana (Universitas Budi Luhur, 2023)
The pervasive internalization of patriarchal norms within Indonesian society perpetuates the victimization of women, particularly evident in cases of intimate partner violence. This study examines the escalating instances of violence against women within personal relationships, be it in marital or dating contexts. Despite the increasing prevalence of such incidents, the measures employed to address and safeguard victims remain inadequate. This paper employs an explanatory analysis method, focusing on two case studies of intimate partner violence (IPV) in both dating and domestic contexts. Utilizing a criminological framework, the analysis aims to scrutinize the pervasive injustice experienced by a significant portion of the female population. The selected case studies serve as illustrative examples to demonstrate the challenges inherent in the legal process, emphasizing the difficulty in access attributed to a law enforcement perspective that has yet to fully embrace a gender justice worldview. The findings of this study draw attention to the nuanced dynamics surrounding IPV in the legal domain. A crucial aspect highlighted is the need for a comprehensive understanding of these dynamics. The investigation extends to social reactions, with the virtual community, or